THE USE OF CISPLATIN IN SPECIAL CONDITIONS - Pratama Putera Tanzil (Sean Institute, 2023)
Cisplatin is a chemotherapy drug used to treat several types of cancer, such as ovarian cancer, testicular cancer, or bladder cancer. The drug can be used as a single treatment or combined with other anticancer drugs. Cisplatin is a chemotherapy drug containing platinum. This drug works by inhibiting the formation of cell DNA so that it can slow down and stop the growth of cancer cells. The drug is also necessary in various special conditions such as pregnant women, nursing mothers, children, geriatrics. The use of Cisplatin in conditions of specificity is cisplatin is not recommended in pregnant women, cisplatin is not recommended in nursing mothers, cisplatin can be used in children, cisplatin can be used in geriatrics.